ANALISIS PENGARUH HARGA, PENDAPATAN, LOKASI, DAN FASILITAS TERHADAP PERMINTAAN RUMAH SEDERHANA (Studi Kasus Perumahan Puri Dinar Mas Semarang) - Ismi Mahardini; Nenik Woyanti (Universitas Diponegoro, 2012)
House is representing requirement of human being base besides food and clothing. There byincrease also society welfare, so from that is human need more various, and one of them needresidence that is house. On of house developers PT. Ajisaka that offered one of proper housingoccupies that is Puri Dinar Mas. However, the problems is decreasing demand of house in Puri MasDinar Resident. Therefore, the purpose of this research was to analyze the influence of factor prices,income, location and facilities to demand of housing on Puri Dinar Mas Resident.The analyzer for this research is using doubled linear regression analysis with program SPSSversion 16.0. Population that used is the Head of Family (KK) as consumers in the Puri Mas DinarResident. While sample that used as much as 100 person (KK) with Methods Random Sampling.Based on result of analysis indicate that price, income, location, and facilities have an effect on todemand of house in Puri Dinar Mas Resident. From the examination of coefficient of determinationhas known that 77,2% from variation of that happened in variable demand of house by togheter ininfluencing by variable price, income, location, and facilities. While the rest equal to 22,8%influenced by other factors. Based on the result of this research we got that facility factor very havingeffect on in demand of house in Puri Dinar Mas Resident. Seen from level of coefficient influencingdemand of house of facility equal to 0,249; location equal to 0,231; income equal to 0,195; and priceequal to 0,149.